Activity profiles and hook-tool use of New Caledonian crows recorded by bird-borne video cameras - Troscianko, Jolyon (Biol Lett, 2015)
New Caledonian crows are renowned for their unusually sophisticated tool behaviour. Despite decades of fieldwork, however, very little is known about how they make and use their foraging tools in the wild, which is largely owing to the difficulties in observing these shy forest birds. To obtain first estimates of activity budgets, as well as close-up observations of tool-assisted foraging, we equipped 19 wild crows with self-developed miniature video cameras, yielding more than 10 h of analysable video footage for 10 subjects. While only four crows used tools during recording sessions, they did so extensively: across all 10 birds, we conservatively estimate that tool-related behaviour occurred in 3% of total observation time, and accounted for 19% of all foraging behaviour. Our video-loggers provided first footage of crows manufacturing, and using, one of their most complex tool types—hooked stick tools—under completely natural foraging conditions. We recorded manufacture from live branches of paperbark (Melaleuca sp.) and another tree species (thought to be Acacia spirorbis), and deployment of tools in a range of contexts, including on the forest floor. Taken together, our video recordings reveal an ‘expanded’ foraging niche for hooked stick tools, and highlight more generally how crows routinely switch between tool- and bill-assisted foraging.